Analisis Spillover Effect Pertumbuhan Ekonomi Antar Kabupaten/Kota di Kawasan Gerbangkertosusila Provinsi Jawa Timur - Agustian Mahendra Putera; Mohammad Wahed (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Uneven economic growth in the Gerbangkertosusila region of East Java raises questions about the extent of spillover effects from economic centers such as Surabaya to surrounding districts and cities. This study aims to analyze the causal relationships in regional economic growth and identify the presence of economic spillover effects within the area. Using a quantitative approach through Granger Causality Test and Vector Error Correction Model (VECM), the research examines Gross Regional Domestic Product (GRDP) constant price (ADHK) data from 2000 to 2023 across six districts/cities in Gerbangkertosusila. The findings reveal both unidirectional and bidirectional causal relationships between several regions, and the presence of both positive (spread effect) and negative (backwash effect) spillovers. These effects reflect complex interdependencies driven by absorptive capacity, infrastructure connectivity, and local government policy. The implications highlight the need for integrated regional development planning to harness inclusive and sustainable economic growth benefits.